Conflict Prevention through Cultural Synergy Model (CPCSM): Collaborative Roles of Opinion Leaders in Sustaining Religious Harmony in Parepare and Tana Toraja - Sulvinajayanti; Ramli; Wahyuddin (FAKULTAS DAKWAH UIN SALATIGA, 2025)
This study aims to explore the collaborative role of opinion leaders, including religious leaders, traditional leaders, academics, government, and popular media, in maintaining diversity while preventing potential religious and culturally based social conflicts in Parepare and Tana Toraja. Through a communication ethnography approach and utilising in-depth interviews, participatory observation as well as thematic and narrative data analysis, this study reveals that local values such as Sipakatau, Sipakainge, Sipakalebbi, Rambu Solo’, Rambu Tuka', and Tongkonan are not only the foundation of harmony, but also produced and distributed through dialogue forums, educational policies, and digital campaigns in a synergistic and non-hierarchical manner. The main outcome of the research is the formulation of the Conflict Prevention through Cultural Synergy Model (CPCSM), which illustrates how religious moderation is built collectively through interactions between opinion leaders. This model underlines the importance of proactive and preventive strategies based on local wisdom and the utilisation of digital media to strengthen social resilience amid diversity. This finding is significant not only as a conceptual contribution to the study of religious communication but also as a practical reference for strengthening public policy and replicating diversity models in other multicultural areas.